Desarrollo de la infraestructura de puertos y aeropuertos para la integración Asia Pacífico - Alonso, Roberto (1999)
Ministers'Forum on Infraestructure Development in the Asia Pacific Region, the Third, China, Hong Kong, may 26-28, 1999